The Big Data Era: What are the Implications for the World of Accounting? - Rokhmat Taufiq Hidayat; Akhmad Khabibi (Majalah Ilmiah Bijak, 2020)
In an era where information technology is developing so rapidly as it is now, contact with technology is inevitable. One that may often be heard is the use of big data. Although the development of big data has begun long before, its growth began rapidly since the Oxford Dictionary included the definition of big data in 2013. The use of big data is thought to have a big influence on the business world, and anything that influences the business world will certainly affect the world of accounting. Does the accountant anticipate these changes? In this article, the author tries to explore what allusions might occur between the world of accounting and big data. Big data will increase the complexity of the accounting world by adding unstructured data in the accounting cycle. This presents a challenge for accountants but can also provide far greater added value if accountants are able to use it well. The results of this study indicate that there are at least 3 areas in the field of accounting that are very likely to be exposed to the use of big data, namely in the process of financial accounting, managerial accounting, and auditing